2021
DOI: 10.3390/app11010373
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Genetic Resources Can Provide Several Animal Models to Explain at the Genetic Level the Diversity of Morphological and Physiological Relevant Traits

Luca Fontanesi

Abstract: The rabbit (Oryctolagus cuniculus) is a unique multipurpose domestic species that has relevant economic impacts in several contexts. This review is focused on rabbit genetic resources that have been mainly bred for the fixation of differentiating features (e.g., exterior traits) that have been already genetically characterized. Several naturally occurring rabbit mutants could be useful as animal models for the investigation of the biological mechanisms determining their characterizing aspects, with translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 122 publications
(207 reference statements)
1
19
0
Order By: Relevance
“…[36,[73][74][75][76]). The large number of rabbit breeds represents a unique and mostly unexplored resource, which can help to dissect the genetic architecture of external traits in this lagomorph species and, as a mirror, also in other mammals [1]. The rabbit is used as an animal model for applied and basic biological studies, mainly where the rodents have demonstrated several limits [77].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[36,[73][74][75][76]). The large number of rabbit breeds represents a unique and mostly unexplored resource, which can help to dissect the genetic architecture of external traits in this lagomorph species and, as a mirror, also in other mammals [1]. The rabbit is used as an animal model for applied and basic biological studies, mainly where the rodents have demonstrated several limits [77].…”
Section: Discussionmentioning
confidence: 99%
“…The European rabbit (Oryctolagus cuniculus), usually simply referred to as rabbit, is the only species that has been domesticated exclusively in western Europe. Its domestication started from the wild populations in the South of France that originally derived from the wild populations of the O. c. cuniculus subspecies spread in the Iberian Peninsula, which experienced a postglacial expansion (reviewed in [1]). Among the possible animal domestication trajectories that have been theorised [2], domestication of the rabbit better matches the directed pathway that does not involve preliminary steps of habituation of animals to human beings and begins with the capture of wild animals, with the aim of controling their breeding and reproduction.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations